«Великий терор» 1937–1938 рр. на Хмельниччині - Місінкевич, Л. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2007)
The article is dedicated to the ways that put into practice the policy of repression in Khmelnitskyi region.